The Identification of Subject Verb Agreement Mistake Committed by Fourth Semester Student Using Corder’s Theory in English Education Department at University of Papua - Dasra, Mimi Enggelina Papua Putri; Sahid, Suardi; Murianty, Riana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to identify the main problems with the Subject-Verb Agreement found in students writing in the English Education major at University of Papua, to know the main problem researcher used Corder’s theory to determine the mistake in student’s essay while their write. This research was conducted on semester 4th students of the University of Papua. The method used is a qualitative descriptive. The findings of the research show that there were a lot of mistakes that occurred in students’ essays. where the highest percentage of error was Omission (43.97%), then Mis-information (29.08%), Addition (20.99%) and the lowest error was Mis-ordering (4.96%). Furthermore, there are several causes of these errors, namely First language influence, language exposure and carelessness. Basically, the causes of the errors that have been exposed above are the sources of error that are found in students' writing. To avoid and reduce those errors, the students should practice and expose themselves to their language targets.